Behavior Patterns in Consuming and Disseminating News and Information in Uinsu Male and Female Students - Arif Indra Hasan Hrp; Andini Nur Bahri (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The objective of this study is to examine and determine how male and female students at the State Islamic University of North Sumatra (UINSU) behave differently in terms of how they consume and share news and information. A quantitative survey with 100 participants from 8 faculties is the methodology employed. SPSS version 25 was used to process the data, and one-way ANOVA was used for data analysis. A questionnaire intended to assess news and information consumption and dissemination was used to gather data. The one-way ANOVA analysis's value of 0.401, which is greater than 0.05, indicates that there is no discernible difference between male and female UINSU students' news and information consumption and dissemination behavior patterns.